PENGARUH KEBIJAKAN DEVIDEN, NET PROFIT MARGIN (NPM) DAN CURRENT RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Rotua Desisari Pardede; Apryanti Monica Sitopu; Yuri Febrina Pardede; Annisa Nauli Sinaga; Jaka Permana (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The objective of the study is to test and analyze the effect of dividend policy, net profit margin and current ratio to corporate value of companies at property and real estate listed in the Indonesia Stock Exchange (IDX) in the period of 2012-2016. The research used some theories of dividend policy, net profit margin and current ratio. The research was used by a quantitative research approach, this research was causal/clausal. The data collection of this research was performed by study documentation. This research uses secondary data types and sources. The research finding revealed that profitability, dividend policy, net profit margin and current ratio simultaneously have a positive effect on corporate value of companies at property and real estate listed in the Indonesia Stock Exchange in the period of 2012-2016. The research concluded that dividend policy, net profit margin and current ratio partially have a positive and significant effect on corporate value of companies at property and real estate listed in the Indonesia Stock Exchange in the period of 2012-2016.